Low-cycle fatigue life of a thermal break system under climatic actions. (1st August 2018) - Keo, Pisey; Le Gac, Benoit; Somja, Hugues; Palas, Frank
Highlights: Experimental testing of a Thermal Break System under low cycle fatigue load. A loading is defined based on the data of the European Climate Assessment and Dataset. Fatigue resistance of the TBS based on the experimental design curve is verified. Yielding of the profiles of the TBS under service climatic actions is found admissible. Parametric study on the effect of the security coefficient is also carried out. Abstract: External insulation is more widely used in Northern and Continental Europe than internal insulation. This technique leads to thermal bridges where the building facade has projecting elements like balconies. The thermal requirements of actual standards lead to restore the continuity of the insulation at the interfaces by using thermal break systems (TBS). These systems are usually made of a box containing the insulation material, and a minimalist structural system able to transmit the shear force and the bending moment from the balcony to the wall. In most cases, structural elements are made of stainless steel, as it is less heat-conducting than normal steel. The paper focuses on a specific TBS that uses shear keys and steel profiles to ensure the transfer of forces. TBS are also submitted to important horizontal cyclic shear deformations, provoked by the variations of the dimensions of the balconies due to climatic effects. The objective of the study presented in the paper is to show that significant yielding under these actions can be accepted during service life. First experimental cyclic loading tests have been performed in order to characterize the behaviour of the TBS, as well as its fatigue strength. Then the loading has been defined on the basis of the database of the ECA&D, the European Climate Assessment and Dataset. Finally, the fatigue resistance of the system has been verified. It is shown that the developed TBS can resist to fatigue loading for great length of balconies, while exhibiting significant yielding during service life.